Reference Specifications: A study on biological control in brazilian organic agriculture - Sousa, Jeremias Marques de; Sampaio, Renata Martins (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2024)
Organic production has an important challenge in the supply of inputs. Bio-inputs for biological control, through reference specifications, are presented as promising solutions. Therefore, this article analyzes the participation of bioinputs for biological control in Brazilian organic agriculture. To this end, it characterized the scenario of organic agriculture and biological control and then carried out, in two stages of research, an analysis of the opinions of experts in organic production. The results were positioned in the expansion of organic production and market, as well as biological control, both activities permeated by public policies. They also pointed out bioinputs as technologies that are little known and little used by organic producers, mainly small and medium-sized ones, a situation also observed for the instruments provided for in the reference specifications. Finally, the results indicated that overcoming this scenario lies in the integration between the policies being implemented, social movements and business actions, associated with the promotion of research and rural extension.